Formulation and Evaluation of Liposomal Based Nanocochleate - Vakhare, Aparna Gajanan; Vankhade, Vikrant P; Atram, Sandip C; Bobade, Nishan N; Pande, Shrikant D (Asian Journal of Pharmaceutical Research and Development, 2024)
Rivastigmine is a parasympathomimetics and a reversible cholinesterase inhibitor. It inhibits both acetylcholinesterase and butylcholinesterase. It is used to treat mild to moderate dementia caused by Alzheimer's or Parkinson's disease. However, its bioavailability is about 36% due to hepatic first-pass metabolism. The plasma half-life of rivastigmine is approximately 1.5 hours. Rivastigmine tartrate-loaded nanococclets (RN) were developed using a trapping method by addition of calcium ions to preformed negatively charged liposomes (RL) prepared by thin film hydration method. Liposomes were optimized by varying the concentrations of disteroylphosphodylcholine (DSPC) and cholesterol. The optimized liposomal batch (RL) containing DSPC (40mg) and cholesterol (10mg) showed mean particle size, zeta potential and entrapment of 112 ± 4 nm, -51.70 ± 7.3 mV and 99.6 ± 4 % for the final form, 51.70 ± 7.3 mV. Observed with efficiency. RN3 which was developed from RL showed 631.4 ± 4 nm, -17 ± 6.5 mV and 99 ± 4.20 %. Encapsulation of RT in nanocochleates is to protect the drug from rapid metabolism, thereby improving bioavailability and ensuring controlled release. In vitro drug release studies showed extended release up to 24 hours, reduced dosing frequency compared to plain drug formulation, nearly 100% of drug was released within 8 hours from pure RT solution, while powder nanococclets released 69% of drug. 8 hours respectively. Stability studies also concluded that nanocochleates are more stable than liposomes.